"The only true people" Linking Maya identities past and present - Beyyette, Bethany J., editor; LeCount, Lisa J., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
A timely and rigorous examination of ethnicity among the ancient Maya, focusing on ethnogenesis and exploring the complexities of Maya identity--how it developed, how it emerged and how it continues to change. Challenges the notion of ethnically homogenous "Maya peoples" for their region and chronology.--Provided by publisher.
The only true people: linking Maya identities past and present
Introduction: on constructing a shared understanding of historical pasts and nearing futures / Bethany J. Beyyette -- Reimaging the world: Maya religious practices and the construction of ethnicity in Mesoamerican frame / Mathew C. Samson -- From ethnogenesis to ethnoexodus: Mayas, Dzulo'ob, and the politics of identity in Yucatán / Juan Castillo Cocom, Timoteo Rodriguez, and McCale Ashenbrener -- Itzaj and Mopan identities in Petén, Guatemala / Charles Andrew Hofling -- Maya ethnogenesis and group identity in Yucatan, 1500-1900 / Matthew Restall and Wolfgang Gabbert -- Differentiation among Maya speakers: evidence from comparative linguistics and from hieroglyphic texts / Martha J. Macri -- Right place, right time: preconditions for ethnogenesis among the classic Maya of the Upper Belize River Valley / Lisa J. LeCount -- He's Maya, but he's not my brother: exploring the place of ethnicity in classic Maya social organization / Damien B. Marken, Stanley P. Guenter, and David A. Freidel -- Considering the edge effect: ethnogenesis and classic period society in the southeastern Maya area / Marcello A. Canuto and Ellen E. Bell -- Copan, Honduras, a multi-ethnic melting pot during the late classic? / Rebecca Storey -- Conclusion / Ed Schortman.
Keywords: Mayas -- Ethnic identity